Coastal Community Education: CCRES dan Sahabat Pulau - Ratu Yunita Sekar; Viena Nurhasanah; Nike Kamarubiani (IKIP Siliwangi Bandung, 2020)
CCRES and Sahabat Pulau are two organization with different basic that provided education program for coastal community. CCRES is an international research project; meanwhile Sahabat Pulau is a voluntary organization. Both targeted Gusung Village, Kabupaten Kepulauan Selayar (an island in South Sulawesi) to be on their programs. This article describes the similarities and the differences between CCRES and Sahabat Pulau in providing educational program for the community in coastal area.